INTERGENERATIONAL COMMUNICATION AS A FACTOR INFLUENCING THE FORMATION OF EDUCATIONAL STRATEGIES AMONG TODAY’S RUSSIAN YOUTH - Chudnovskaia, Irina; Lipatova, Mariia (Revista Inclusiones, 2020)
The study is part of current research analyzing criteria of using the labor potential of youths as one of the major resources in any country. The research subject is the new generation born at the turn of the century and communicating in the context of the digitalization of society to which the scientific discourse attributes a set of generalized distinctive feature yet to be validated scientifically. One of such attributive features is individualism and communicative distancing from parents. The aim of the present study is to detect and characterize what role the communicative impact of parents plays in the formation of educational strategies among present-day young people in Russia after their graduation from high school and during their studies for a Bachelor’s or Master’s degree, a period that can be described as a time of uncertainty. Intergenerational communication is defined as a social activity focusing on two main aspects, the symbolical and resource ones, as a part of the so-called reflexive project of today’s youths aimed at building their identity and as a factor in the maintenance of the intrapersonal communication during periods of uncertainty throughout their lives.